2018
DOI: 10.1088/1361-6455/aab541
|View full text |Cite
|
Sign up to set email alerts
|

Collective modes in multicomponent condensates with anisotropy

Abstract: We report the effects of anisotropy in the confining potential on two component Bose-Einstein condensates (TBECs) through the properties of the low energy quasiparticle excitations. Starting from generalized Gross Pitaevskii equation, we obtain the Bogoliubov de-Gennes (BdG) equation for TBECs using the Hartree-Fock-Bogoliubov (HFB) theory. Based on this theory, we present the influence of radial anisotropy on TBECs in the immiscible or the phase-separated domain. In particular, the TBECs of 85 Rb -87 Rb and 1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 63 publications
(93 reference statements)
0
6
0
Order By: Relevance
“…Though the eigenvalues are printed in hfb2d2s.out, for other detailed computations like the mode evolution as a function of anisotropy and interaction parameters, the energy eigenvalues are also stored in the output file eigenvalue.out. Such data is useful in studies like our previous works [16,17], where we have shown the mode evolution as a function of various parameters using these package. It is to be mentioned that, the energy eigen values, chemical potentials and total energy of the system, calculated in this package are in units of ω x .…”
Section: Output Datamentioning
confidence: 94%
See 2 more Smart Citations
“…Though the eigenvalues are printed in hfb2d2s.out, for other detailed computations like the mode evolution as a function of anisotropy and interaction parameters, the energy eigenvalues are also stored in the output file eigenvalue.out. Such data is useful in studies like our previous works [16,17], where we have shown the mode evolution as a function of various parameters using these package. It is to be mentioned that, the energy eigen values, chemical potentials and total energy of the system, calculated in this package are in units of ω x .…”
Section: Output Datamentioning
confidence: 94%
“…To examine the effect of anisotropy in the trapping parameter one can consider AL < 1 (corresponding to ω y ω x , the TBEC is elongated along y axis) or AL > 1 (corresponding to ω x ω y , the TBEC is elongated along x axis). In our recent work [17], we have considered the effect of anisotropy in 85 Rb -87 Rb TBEC at zero temperature for AL > 1. To make the system quasi-2D a large value of anisotropy parameter along axial direction LAMBDA = 12.5 is chosen so that the condition µ ω z is satisfied.…”
Section: Initializementioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the experimental probing of an ultracold-gas interface was recently shown for a Bose-Fermi system [24] while multiple studies stipulate the important role of interface physics in explaining equilibrium configurations of current-day experimental situations [25][26][27][28]. Interface statics [29] and especially interface dynamics of multi-component condensates gained substantial recent attention [30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the Rabi coupling stabilizes the superfluid phase in coupled BECs in optical lattices [32]. A variety of collective modes, namely, Nambu-Goldstone, slosh, bifurcation modes were studied in the trapped two-component quasitwo-dimensional (quasi-2D) BECs [33,34].…”
Section: Introductionmentioning
confidence: 99%